2017
DOI: 10.1111/tpj.13553
|View full text |Cite
|
Sign up to set email alerts
|

Diverse genome organization following 13 independent mesopolyploid events in Brassicaceae contrasts with convergent patterns of gene retention

Abstract: Hybridization and polyploidy followed by genome-wide diploidization had a significant impact on the diversification of land plants. The ancient At-α whole-genome duplication (WGD) preceded the diversification of crucifers (Brassicaceae). Some genera and tribes also experienced younger, mesopolyploid WGDs concealed by subsequent genome diploidization. Here we tested if multiple base chromosome numbers originated due to genome diploidization after independent mesopolyploid WGDs and how diploidization affected po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
95
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 106 publications
(196 reference statements)
8
95
0
Order By: Relevance
“…Our observation across multiple species is consistent with post-polyploid genome evolution as dosage-balance may drive the convergent retention of genes. Previous empirical studies supported that gene dosage balance plays an important role in gene retention following gene and genome duplications (Freeling 2009;Session et al 2016;Mandáková et al 2017) . Other hypotheses of duplicate gene retention such as neo-and subfunctionalization are also important in duplicate gene retention, but only the DBH predicts a convergent pattern of gene retention following polyploidy across multiple species (Kondrashov and Kondrashov 2006;Freeling 2009) .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Our observation across multiple species is consistent with post-polyploid genome evolution as dosage-balance may drive the convergent retention of genes. Previous empirical studies supported that gene dosage balance plays an important role in gene retention following gene and genome duplications (Freeling 2009;Session et al 2016;Mandáková et al 2017) . Other hypotheses of duplicate gene retention such as neo-and subfunctionalization are also important in duplicate gene retention, but only the DBH predicts a convergent pattern of gene retention following polyploidy across multiple species (Kondrashov and Kondrashov 2006;Freeling 2009) .…”
Section: Discussionmentioning
confidence: 98%
“…This biased pattern was also found among WGD paralogs in an outgroup species, Ixodes scapularis (deer tick), and suggests that it may be consistent across arthropods. Previous studies in plants have found that similar functional categories of genes have been maintained following different genome duplication events Rody et al 2017) , although there are o en idiosyncratic patterns observed across families (Maere et al 2005;Barker et al 2008;Li et al 2016;Mandáková et al 2017) . The 20 insect transcriptomes included in our GO category analyses represent diverse hexapod (SI 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brassica for example, the variation in base chromosome numbers is the result of multiple and independent diploidizations from the mesohexaploid ancestor (Lysak et al, 2007;Mandáková et al, 2017). Indeed, the stochasticity of polyploid drop, not WGD, is thought to be a major contributor to speciations and radiations (Figure 1).…”
Section: Post-polyploidy Diploidization a Cradle For Diversificationmentioning
confidence: 99%
“…Successive WGDs have occurred in multiple lineages: As indicated, angiosperms have experienced multiple WGDs, and recursive WGDs among the Brassica crops that include cauliflower, broccoli and cabbages have been precisely mapped recently 58 . The vertebrate animals emerged from the invertebrates approximately 500 Mya via two sequential rounds of WGD (2R-WGD) 59 .…”
Section: Common Themes From Recent Reconstructions Of Ancient Whole-gmentioning
confidence: 99%